Capital imports into sterling countries - Conan, A. R. (London : Macmillan; New York : St. Martin's Press, 1960)
This book examines the post-war movement of capital to certain sterling countries. For each of these countries an attempt is made to measure the capital inflow, assess its character and its source. The results are then assembled to give a synoptic view of the whole field.
Includes index
Includes bibliographical references
usc 20/04/18
Loans
Keywords: Investments, Foreign; Sterling area